Design a Portable Lifting Machine for Transfer Heavy Bricks in Construction Sites - Jamil, Nurul Nazihah; Azlan, Mohd Azwir (Research Progress in Mechanical and Manufacturing Engineering, 2024)
The construction industry in Malaysia is witnessing significant growth, particularly in the residential sector, necessitating faster and safer construction methods. Manual bricklaying, a vital aspect of construction, poses inherent risks to workers due to the physical strain involved. This project proposes portable lifting equipment to speed bricklaying and improve worker safety. The project begins with a comprehensive analysis of the hazards associated with manual bricklaying, emphasizing the prevalence of musculoskeletal disorders and the potential for severe injuries among workers. The primary objective is to design a compact and user-friendly machine capable of efficiently lifting and transporting heavy bricks within construction sites. The scope of the study encompasses the design and development of a portable lifting machine with specific parameters: a height range of 3.5 to 5 metres, a maximum payload of 80.51 kg, and a capacity to transfer 2368 bricks per hour. SolidWorks software is used to create comprehensive 3D models, motion analysis, simulations, and engineering drawings for product precision and functionality. The device’s final design, engineered with anti-corrosion features, high durability, and standardized components, ensures longevity and reliability even in challenging construction environments. Expected to outperform manual lifting techniques, this portable machine stands as a cost-effective and practical solution to elevate productivity in construction practices. Finally, this study shows how George E. Dieter’s principles were used to create a portable brick lifting machine that meets industry needs. This device could revolutionize bricklaying, improving construction efficiency, safety, and overall performance.